Entrepreneurs in the New Economy: Immigration and Sex Effects in the Montreal Metropolitan Area - Paré, Sylvie; Therasme, Kelogue (Journal of International Entrepreneurship, 2010)
The recent literature on women’s entrepreneurship shows that they are underrepresented in the main stream economy when compared to their male counterparts, a phenomenon typically observed in other urban contexts. Approximately 30% of the entrepreneurs in the Montreal metropolitan area are women, active in a variety of sectors of the general economy. Their underrepresentation is still greater in the new economy, that is, those sectors that are knowledge-based and/or specialized in information technologies and communications. In this article, we examine the place of female entrepreneurs in the larger economy and in the new economy as related to their immigrant and/or ethnic origins. We seek in this paper to establish a comparative analysis of the situation of women entrepreneurs in immigrant-origin groups, focusing our attention on both the presence of women in entrepreneurial positions and the differential impact associated with membership in an immigrant-origin group. Based on data derived from Scott's Directory of 2007, we first determined an operational definition of the new economy and then analyzed the data from the perspective of sex and ethnic/immigrant origin. New economy enterprises represent approximately 12% of businesses in the Montreal metropolitan area, the majority of which are of the knowledge-based variety, and there is a relative, statistically significant absence of women from such enterprises. At the same time, there is a significantly greater presence of women drawn from minority groups, that is, from groups other than the Anglo-Canadian and French-Canadian dominant groups.
Keywords: Femmes; Travail

Diversité et pluralisme à Montréal: des perceptions, des faits - Paré, Sylvie (Montréal, aujourd'hui et demain. Politique, urbanisme, tourisme, 2009)